Control of tsetse flies in West Africa : optimizing the use of the sterile insect technique - (:unkn) unknown (My University, 2015)
In sub-Saharan Africa, nearly 10 million km² of land, the most fertile for animal and agricultural productions, are infested with tsetse flies limiting all development initiatives for sustainable agriculture. Tsetse flies transmit trypanosomes that cause human and animal african trypanosomosis, a debilitating disease of humans (sleeping sickness) and livestock (nagana). In 2000, the African Heads of State and Government decided to increase efforts to address the tsetse and trypanosomosis problem on the African continent and created the Pan-African Tsetse and Trypanosomosis Eradication Campaign (PATTEC). In this context, the Government of Senegal initiated a tsetse eradication program in the Niayes area using a Glossina palpalis gambiensis strain originating from Burkina Faso. The objective of this thesis was to optimize the use of the sterile insect technique (SIT) in West Africa in order to control the tsetse flies. A system to transport mature pupae over long distances has been developed and validated for male G. p. gambiensis pupae produced and irradiated either in Bobo-Dioulasso, Burkina Faso or in Bratislava, Slovakia (irradiation done in Seibersdorf, Austria) and then transported by air to Dakar, Senegal. The system, constituted of an insulated box and S8 packs, allowed the maintenance of pupae at a temperature of 10 ± 3°C and their transport during 2-3 days to the emergence center of ISRA, where they molted into sterile males which were used for the sterile insect technique.A quality control was carried out on a sample of 50 pupae from each batch (at least 2 batches per shipment) to determine the flight ability of sterile males and their survival under stress conditions (without feeding). The remaining emerging pupae were released in the target area of the eradication programme and were considered as control group. The described protocol for quality control will allow accurate monitoring of the quality of sterile males used in operational era
Keywords: African Research